Transcriptome data for an ancient ‘living-fossil’ mollusc, Entemnotrochus rumphii - Wang, Yunan; Wang, Haiyan; Song, Hao (Scientific data, 2024)
The Pleurotomarioidea, commonly referred to as slit shells, constitute one of the most ancient and enduring lineages within the phylum Mollusca, with its fossil record tracing back to the Upper Cambrian epoch. Its rareness and evolutionary antiquity surpass even that of the nautilus. In this study, we conducted the first transcriptome sequencing and analyses of Entemnotrochus rumphii (Schepman, 1879), a representative species of Pleurotomarioidea. Full-length transcriptome sequencing of E. rumphii was performed using the PacBio Sequel II platform with SMRT technology. A total of 64.38 gigabytes of data and 964,550 polymerase reads were generated, resulting in 28,068,998 subreads after data filtering. After de-duplication, correction, and clustering, we identified 19,273 genes. Additionally, next-generation sequencing was performed on 11 tissues of E. rumphii . This investigation provides a detailed portrayal and analytical scrutiny of its transcriptomic landscape.